Behind the smile: qualitative study of caregivers' anguish and management responses while caring for someone living with heart failure. Issue 7 (20th July 2017) - Wingham, Jennifer; Frost, Julia; Britten, Nicky
Abstract : Background: Caregivers support self-management in heart failure but often experience stress, anxiety and ill health as a result of providing care. Aims: 1. To identify the factors that contribute to the experience of anguish. 2. To understand how caregivers learn to live with what is frequently a challenging and demanding role. Methods: Individual interviews with caregivers who had been caring for someone with heart failure for a minimum of 6 months. We used thematic analysis to inductively analyse transcripts. Results: Twenty-two caregivers, from three centres in the United Kingdom, took part in individual interviews. The caregivers were aged between 39 and 84 years, and six were men. Twenty were in spousal or partner relationships. We found that caregivers often hide the extent of their emotional stress or anguish. We identified four main themes with explanatory subthemes—emotional impact (fear for the future and sense of hopelessness), role definition (changing sense of who I am, reduced resilience, learning care skills, role conflict and changing role), exclusion (exclusion by the cared-for person and by health professionals and feeling alone) and ignoring one's own health—that were associated with anguish. From these findings, we produced a caregiver needs assessment model in the context of caring for a person with heart failure. Conclusions and implications for practice: Caregivers have many unmet and hidden needs. Primary care health professionals are well placed to meet the needs of caregivers. The model may be used by health and social care professionals to identify needs and to provide caregivers with targeted practical and emotional support; and for researchers developing interventions to enhance self-management in heart failure.